Perception on brand positioning of three star hotels in Kuala Terengganu, Terengganu / Zainuddin Zakaria … [et al.] - Zakaria, Zainuddin; Ismail, Mohd Khairi; Mat Rashid, Kartini; Abdul, Shaiful Azlan; Ahmad Ramli, Faten Fatehah (Universiti Teknologi MARA, Perlis, 2023)
The purpose of brand positioning is to change the perception of prospective customers compared to other brands in the same product category. Many business organisations try to steer the customer's mind on the target brand and its advantage in the market. To determine whether the positioning of a certain brand is a success or not, a company should observe whether its brand is salient or not to the customers. Positioning or brand positioning includes choosing a particular product characteristic from the whole set of features associated with the brand. The main aim of this research is to determine the factors influencing the brand positioning of three-star hotels among residents in Kuala Terengganu. The first objective is to examine the relationship between the price and brand positioning of three-star hotels. The second objective is to determine the effect of brand image on the brand positioning of a three-star hotel. The third objective is to define the value of the brand positioning of a three-star hotel. The researcher disseminated 384 sets of questionnaires to 384 respondents in Kuala Terengganu and used SPSS version 20 to analyse the data. By using the data gathered, the researchers can produce frequency analysis, descriptive statistical analysis, Pearson test correlation analysis, regression analysis, hypothesis testing, and also the interpretation of objectives. The finding shows that two independent variables (price and brand image) have a significant relationship with the brand positioning of three stars hotels. Brand image is the vision of hotels in the industry more than what hotels' records show and the price represents the standard of service as perceived by the customers. Positioning is the use of marketing to project differentiation in the hotel and its services to targeted customers. Building and maintaining a strong brand positioning is critical in that it will help create a positive image and create unique perceptions among present and potential customers. A hotel with a positive brand positioning will transform a satisfied customer into loyal guests.